Phytochrome activates the plastid-encoded RNA polymerase for chloroplast biogenesis via nucleus-to-plastid signaling - Yoo, Chan Yul (Nat Commun, 2019)
Light initiates chloroplast biogenesis by activating photosynthesis-associated genes encoded by not only the nuclear but also the plastidial genome, but how photoreceptors control plastidial gene expression remains enigmatic. Here we show that the photoactivation of phytochromes triggers the expression of photosynthesis-associated plastid-encoded genes (PhAPGs) by stimulating the assembly of the bacterial-type plastidial RNA polymerase (PEP) into a 1000-kDa complex. Using forward genetic approaches, we identified REGULATOR OF CHLOROPLAST BIOGENESIS (RCB) as a dual-targeted nuclear/plastidial phytochrome signaling component required for PEP assembly. Surprisingly, RCB controls PhAPG expression primarily from the nucleus by interacting with phytochromes and promoting their localization to photobodies for the degradation of the transcriptional regulators PIF1 and PIF3. RCB-dependent PIF degradation in the nucleus signals the plastids for PEP assembly and PhAPG expression. Thus, our findings reveal the framework of a nucleus-to-plastid anterograde signaling pathway by which phytochrome signaling in the nucleus controls plastidial transcription.